2016
DOI: 10.1186/s12866-016-0787-3
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression of Chlamydia trachomatis major outer membrane protein in E. Coli outer membrane as a substrate for vaccine research

Abstract: BackgroundChlamydia trachomatis is a human pathogen which causes a number of pathologies, including genital tract infections in women that can result in tubal infertility. Prevention of infection and disease control might be achieved through vaccination; however, a safe, efficacious and cost-effective vaccine against C. trachomatis infection remains an unmet medical need. C. trachomatis major outer membrane protein (MOMP), a β-barrel integral outer membrane protein, is the most abundant antigen in the outer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Structural elucidation of MOMP has been hampered by the requirement for detergents to keep the membrane protein in solution during purification, as well as the lack of a recombinant expression system that preserves MOMP in its native conformation. Despite increasing efforts to express recombinant MOMP, 28 purification and reconstitution remain problematic, and extracting MOMP in its native form from Chlamydia preparations appears to be the optimal solution for the purpose of structure determination.…”
Section: Introductionmentioning
confidence: 99%
“…Structural elucidation of MOMP has been hampered by the requirement for detergents to keep the membrane protein in solution during purification, as well as the lack of a recombinant expression system that preserves MOMP in its native conformation. Despite increasing efforts to express recombinant MOMP, 28 purification and reconstitution remain problematic, and extracting MOMP in its native form from Chlamydia preparations appears to be the optimal solution for the purpose of structure determination.…”
Section: Introductionmentioning
confidence: 99%
“…5b). These multimeric structures are not evident in recombinant MOMP produced in traditional E. coli expression systems with the exception of the Wen et al (13) study in which MOMP is target-expressed in the E. coli outer membrane. This suggests that the environment in which MOMP sits remains critical for correct protein folding.…”
Section: Cell-free Production Of Functional and Immunogenic Mopn-mompmentioning
confidence: 96%
“…mation such as oligomer formation (12,46). It is noteworthy that in a recent study, Wen et al (13) were able to express recombinant MOMP on E. coli outer membrane that allowed for native-like oligomer formation. They further demonstrated that the oligomer formation is critical for effective immunogenicity (13).…”
Section: Cell-free Production Of Functional and Immunogenic Mopn-mompmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the combination of some the above-mentioned strategies, namely, Bcodon harmonization,^use of low copy number vectors with moderate strength, suitable leader sequences, and optimization of cell culture conditions, increased targeting to E. coli outer membrane of Chlamydia trachomatis major outer membrane protein was observed and the formation of inclusion bodies avoided (Wen et al 2016). On the other hand, prokaryotic expression vectors using the rhaB promoter which are almost completely repressed until induced can be suitable for the expression of toxic proteins (Giacalone et al 2006).…”
Section: Genetic-level Strategiesmentioning
confidence: 99%